Pathogenesis and treatment of chronic rhinosinusitis from the perspective of sinonasal epithelial dysfunction - He, Yuanqiong; Fu, Yijie; Wu, Yuqi; Zhu, Tianmin; Li, Hui (Frontiers in Medicine, 2023)
Background Chronic rhinosinusitis (CRS) is a clinical syndrome primarily characterized by long-term mucosal inflammation of the nasal cavity and sinuses. The pathogenesis of CRS is still unclear due to its high heterogeneity. A number of studies have recently focused on the sinonasal epithelium. Thus, there has been a quantum leap in awareness of the role of the sinonasal epithelium, which is now understood as an active functional organ rather than simply an inert mechanical barrier. Undoubtedly, epithelial dysfunction plays a vital role in the onset and development of CRS. Objective In this article, we discuss the potential contribution of sinonasal epithelium dysfunction to CRS pathogenesis and explore a few current and developing therapeutic options targeting the sinonasal epithelium. Results Impaired mucociliary clearance (MCC) and an abnormal sinonasal epithelial barrier are usually considered to be the main causative factors in CRS. Epithelial-derived bioactive substances, such as cytokines, exosomes, and complements, play a vital role in the regulation of innate and adaptive immunity and contribute to the pathophysiological alterations of CRS. The phenomena of epithelial–mesenchymal transition (EMT), mucosal remodeling, and autophagy observed in CRS offer some novel insights into the pathogenesis of this disease. In addition, existing treatment options targeting disorder of sinonasal epithelium can help to relieve the main symptoms associated with CRS to some extent. Conclusion The presence of a normal epithelium is fundamental for maintaining homeostasis in the nasal and paranasal sinuses. Here, we describe various aspects of the sinonasal epithelium and highlight the contributions of epithelial dysfunction to CRS pathogenesis. Our review provides sound evidence of the need for in-depth study of the pathophysiological alterations of this disease and for the development of novel epithelium-targeting alternative treatments.